Dynamics of HSD17B3 expression in human fetal testis: implications for the role of Sertoli cells in fetal testosterone biosynthesis - Planinic, Ana; Maric, Tihana; Himelreich Peric, Marta; Jezek, Davor; Katusic Bojanac, Ana (Frontiers in Cell and Developmental Biology, 2024)
Androgens play a pivotal role in shaping male sexual characteristics, with testosterone being an essential hormone in orchestrating various developmental processes. Testosterone biosynthesis involves a series of enzymatic reactions, among which the 17β-hydroxysteroid dehydrogenase type 3 (HSD17B3) holds significance. While its role in adult Leydig cells is well established, its localization and importance during the fetal period remain less known, especially in humans. This study aims to delineate the dynamics of HSD17B3 expression in human fetal testes to clarify the contribution of specific cell types to testosterone biosynthesis. Using immunofluorescence staining, we investigated the expression pattern of HSD17B3 in human fetal and adult testicular tissues. The findings of this study revealed a distinct temporal and cellular expression pattern of HSD17B3 protein in the fetal period. We detected its expression exclusively in Sertoli cells, the highest during the second trimester. This unique localization suggests the inclusion of fetal Sertoli cells in testosterone production during the critical masculinization-programming window. Furthermore, we demonstrated a shift in HSD17B3 expression from Sertoli cells to Leydig cells in adulthood, corroborating findings from rodent studies. This study sheds light on the intricate, still underexplored regulation of steroidogenesis during fetal development, whose disturbance might lead to testicular dysgenesis. Further research is warranted to elucidate the regulatory pathways governing the expression of HSD17B3 and its transition between Sertoli and Leydig cells, potentially paving the way for novel therapeutic interventions in disorders of sexual development.